STUDI POLA PERSEBARAN DEPOT AIR MINUM ISI ULANG DIKECAMATAN NANGGALO - Bayu Rahmad; Nina Ismayani; Hary Febrianto (Jurnal Azimut, 2023)
This study examines the distribution of drinking water refilling business locations, to determine the distribution scheme of drinking water refilling businesses, and to determine the factors that influence the location of drinking water refilling business selection in Nanggalo District. This study used mixed methods research. For mapping the distribution of drinking water refilling businesses using geographic information systems (GIS), analysis of the distribution of drinking water refilling businesses using triangulation methods, analysis of nearest neighbors to determine patterns and distribution of businesses. Based on the results of the study, it can be concluded that there are 52 storage points in Nanggalo District spread across 6 districts. The distribution scheme, repeating the filling of water and beverages in Nanggalo sub-district, has a random pattern. Factors that influence the selection of the location of the drinking water refill business in Nanggalo District are accessibility, population density, production costs, according to recommended factors.